Divide and rule: managing minorities in interwar Poland - Fedorowycz, D (2016)
In this thesis I address the following puzzle: What explains the presence of the relatively high number of ethnic minority organizations in multinational states, particularly in cases where (a) relations between the titular and minority groups are hostile; (b) the state pursues discriminatory group-level policies vis-à-vis its minorities; (c) state capacity to repress is evident; and (d) the regime is governed by a dominant group, or what can be called a "core nation"? More specifically, the variation I seek to understand through this research is why some political organizations claiming to represent a restive ethnic minority group are banned by state authorities and excluded from public life, while others, which claim to represent the same ethnic group, are allowed to operate. Currently, well-established scholarly literature on state-ethnic minority group relations only focuses on part of the puzzle: it takes the point of view that repression is central in managing opposition, and accordingly has focused only on the reasons that states ban certain organizations. The intent of this study, however, is to change this dominant perspective by examining the question from a different angle, asking why states allow minority ethnic organizations to operate. Indeed, not always do repressive regimes that have the capacity to ban organizations representing a restive minority do—repression is relatively infrequent and selective. My contention instead is that if a multi-ethnic state is faced with a potentially hostile ethnic group, it prefers organizational pluralism which allows it to divide and rule the minority, even if repression is a viable option. This theory differs from existing ones by arguing that states choose to encourage organizational pluralism in ethnic minorities and that, if plurality is absent within an ethnic group, a state may even promote it. I test this hypothesis on the case of interwar Poland (1918-1939). I reconstruct the intentions of policy makers using process-tracing analysis and extensive archival research of the Ministry of Interior (Ministerstwo Spraw Wewnętrznych, or MSW), the main organ responsible for formulating minority policies, and its strategies for governing Ukrainian, Belarusian, German, and Jewish political organizations throughout the interwar period.